Analisis CAR dan ISR terhadap ROA Perbankan Syariah yang Terdaftar di JII Periode 2015-2019 - Astuti, Yuli (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
The purpose of this research is to find out whether there is an effect of Capital Adequacy Ratio and Islamic Social Responsibility on Return On Assets both in terms of partial and simultaneous testing. Collecting data in this study is to use secondary data from the financial statements of Islamic companies listed on the Jakarta Islamic Index. By using two blades of analysis, namely simple linear regression analysis and multiple linear regression analysis. Based on the results of simple regression analysis, it is known that partially CAR affects ROA and partially ISR affects ROA. Then simultaneously CAR and ISR influence ROA. Therefore, the role of profit in the company has an influential role, because the main objective of the company's operations is to achieve maximum profit. Information on profit achievement is not only useful for external parties such as the public as users of Islamic financial institutions as service companies and internal parties as parties who carry out or run the company in order to determine steps how to run the company to make a profit.